THE IMPACT OF INDONESIA-TIONGKOK COOPERATION ON THE ECONOMY RIAU (Study Case: CHINA ASEAN EXPO 2015) - Wulandari, Rosi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describes the impact of Indonesia-Tiongkok cooperation on the economy of Riau ( study case : China ASEAN Expo 2015). Many sectors owned by Indonesia that have a big role in the Indonesian economy as a foreign ax and create jobs. Indonesia has regions that are rich in economic potential that can push the economy of the country, one of which is Riau. Riau has a lot of potential, in addition to the export commodity sector is now the provincial government of Riau is building the tourism sector and creative economy as supporting regional PAD in the long term.The method used in this research is qualitative. All the data and informations obtained from book, journals, articles, internet, and another media. The focus of this research is how the impact of cooperation between Indonesia and Tiongkok to economy of Riau. This research use liberalism perspective and international cooperation theory.The impact of that cooperation for economy of Riau is increasing PAD riau from 2015-207, that is Rp. 3.476 Trilions on 2015, Rp. 3.496 Trilions on 2016, and Rp. 4,535 Trilions on 2017.Key words: cooperation, liberalism, economy of riau